Collaborative inquiry in the EFL classroom: exploring a school related topic with fifth graders - Gómez Gutiérrez, Ana Janneth (Colombian Applied Linguistics Journal, 2018)
This action research study reports an inquiry based learning process in which fifth graders worked collaboratively by examining a local topic (free school snack) from their school context. Collaborative inquiry was used as a way to promote elementary students’ reflections in the EFL classroom drawing on Vygotsky’s ideas about learning mediated by social and material contexts (Lee & Smagorinsky, 2000). The EFL curriculum was organized around students’ communities and realities as relevant resources for language learning (Sharkey, Clavijo & Ramirez, 2016). Lessons were organized around students’ knowledge about the free daily snack that school provides to all children and what they wanted to learn about the topic. In this sense, Dewey’s (1997) idea of learning as experience was implemented through an inquiry curriculum with students. Findings suggest that through a classroom project, fifth graders developed inquiry skills and digital, visual, oral, and written literacies while learning together through collaboration. Inquiring in the language classroom evidenced the use of languages (Spanish and English) as the means to learn about meaningful content beyond English grammar lessons. It also led to individual reflections about the challenges of working together as well as about school coexistence understood as the way all the members of an educational community relate to each other.